Product Demand Shifts and Wage Inequality - Marco Leonardi (Institute for the Study of Labor (IZA), 2003)
The UK and the US have experienced both rising skill premia and rising employment of skilled workers since the 1980s. These trends are typically interpreted as concurrent shifts of relative skill supplies and demands, and the demand shifts are attributed to skill-biased technological change or changes in international trade patterns. If more skilled workers demand more skill-intensive goods, then an exogenous increase in relative skill supplies will also induce a shift in relative demand. This channel reduces the need to rely on technology and trade to explain the patterns in the data. I illustrate this mechanism with a simple twosector general equilibrium model. The empirical part demonstrates that in the UK more educated and richer workers demand more skill-intensive goods. Calibration of the model suggests that this induced demand shift can explain 3% of the total relative demand shift in the UK between 1981 and 1997. The baseline model only explains between-industry shifts in skill upgrading and wage inequality, while empirically, most of these changes took place within industries. An extension of the model with different qualities of goods and labor can also explain some of the within-industry changes.
Keywords: J31; J21; 330; wage inequality; demand shifts; income elasticity; Lohnstruktur; Qualifikation; Hochqualifizierte Arbeitskräfte; Gesamtwirtschaftliche Nachfrage; Produktqualität; Einkommenselastizität; Mehr-Sektoren-Modell; Theorie; Großbritannien